Automobile paint surface protective film and preparation method thereof
By using modified nano-titanium dioxide and nano-zinc oxide combined with organic ultraviolet absorbers in automotive paint protection films, a multi-layered ultraviolet protection mechanism is formed, solving the problem of insufficient ultraviolet blocking in existing technologies and achieving long-lasting protection.
Patent Information
- Application Number
- CN202511528407.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-03-06
AI Technical Summary
Existing automotive paint protection films are insufficient in blocking ultraviolet rays and fail to provide long-term protection.
Nano-titanium dioxide and nano-zinc oxide are used as inorganic ultraviolet blocking agents. They are modified and grafted with γ-glycidyl etheroxypropyltrimethoxysilane and combined with 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole organic ultraviolet absorber to form a composite ultraviolet protection mechanism, which realizes the reflection, scattering and absorption of ultraviolet rays.
It provides long-lasting UV protection for automotive paint, improves UV blocking effectiveness, extends the lifespan of automotive paint, and maintains its aesthetic appeal.
Abstract
Description
Technical Field
[0001] This invention relates to the field of protective films, and more specifically to an automotive paint protective film and its preparation method. Background Technology
[0002] Automotive paint protection film is a functional polymer film applied to the paint layer of a car's exterior. Its main function is to physically isolate the paint from the external environment, thereby resisting damage to the paint caused by natural or man-made factors such as stone impacts, minor scratches, acid rain corrosion, bird droppings, and ultraviolet radiation. With the upgrading of the automotive consumer market and the increasing demand of car owners for vehicle exterior maintenance, this type of product has been widely used because it can extend the life of the original paint and maintain its appearance to a certain extent. Its base material is mostly composed of thermoplastic polyurethane (TPU) or multilayer co-extruded polyester.
[0003] Chinese patent application CN118755122B discloses a hydrophobic and stain-resistant automotive paint protection film and its preparation method, relating to the field of polymer materials technology. In preparing the hydrophobic and stain-resistant automotive paint protection film, the invention involves reacting diethyl phosphite with 1,3-propanediol to obtain a dihydroxyphosphate monomer; polymerizing 1-chloromethyl-2,4-diisocyanobenzene with the dihydroxyphosphate monomer and 2,2-3,3-4,4-5,5-octafluoro-1,6-hexanediol to obtain polyurethane; reacting the polyurethane with 2,2,6,6-tetramethyl-4-piperidinyl methacrylate to obtain a pre-modified polyurethane; reacting the pre-modified polyurethane with dopamine to obtain a modified polyurethane; reacting nano-kaolin with 3-mercaptopropyltriethoxysilane and but-3-enrichedoric acid sequentially to obtain modified nano-kaolin; and melt-blending the modified polyurethane and modified nano-kaolin and then calendering to obtain the hydrophobic and stain-resistant automotive paint protection film. However, this solution only adds conventional UV absorbers and does not deeply optimize the UV blocking mechanism, which may result in insufficient long-term protection. Summary of the Invention
[0004] The purpose of this invention is to provide an automotive paint protection film and its preparation method to solve the problems existing in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a protective film for automotive paint, wherein the protective film is prepared from an ultraviolet blocking agent, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and antioxidant tris(2,4-di-tert-butylphenyl) phosphite; wherein the ultraviolet blocking agent is prepared from nano-titanium dioxide, nano-zinc oxide, aqueous ethanol solution, γ-glycidyl etheroxypropyltrimethoxysilane, and acetic acid.
[0006] Furthermore, the particle size of the nano zinc oxide is 20-30 nm.
[0007] Furthermore, the particle size of nano-titanium dioxide is 20-30 nm.
[0008] Furthermore, the number average molecular weight of thermoplastic polyurethane elastomer particles is 80,000-150,000.
[0009] Furthermore, a method for preparing an automotive paint protection film includes the following steps: (1) Add nano titanium dioxide and nano zinc oxide to an ethanol aqueous solution with a mass fraction of 50-60%, treat with an ultrasonic device with a power of 500-600W for 30-40 minutes, then add γ-glycidoxypropyltrimethoxysilane, adjust the pH value to 4-5 with acetic acid, stir in a sealed container at 50-60℃ and 200-300rpm for 3-4 hours, filter, wash with anhydrous ethanol 2-4 times, and then place in a vacuum drying oven and vacuum dry at 70-80℃ for 4-6 hours to obtain an ultraviolet blocking agent; (2) The UV blocker, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole UV absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite obtained in step (1) are put into a mixer and mixed at a speed of 800-1200 rpm at room temperature for 10-15 minutes to obtain a premix; the premix is fed into a twin-screw extruder for melt blending and granulation, and after extrusion, water cooling and pelletizing, a composite functional masterbatch is obtained; (3) The composite functional masterbatch obtained in step (2) is mixed with thermoplastic polyurethane elastomer particles at a mass ratio of 1:(3-5). The mixture is then added to a single screw extruder, and the melt is cast through a T-die to a cooling roller to form a protective film.
[0010] Furthermore, in step (1), the mass ratio of nano-titanium dioxide, nano-zinc oxide, aqueous ethanol solution and γ-glycidyl etheroxypropyltrimethoxysilane is (5-15):(5-15):(100-200):(4-6).
[0011] Furthermore, in step (2), the mass ratio of the ultraviolet blocking agent, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite is (15-25):(70-80):(3-8):(0.5-2):(0.5-2).
[0012] Furthermore, the processing temperature range of the twin-screw extruder in step (2) is set as follows: Zone 1 160-165℃, Zone 2 165-170℃, Zone 3 170-175℃, Zone 4 175-180℃, and Die head 180-185℃, with a screw speed of 200-400 rpm and a length-to-diameter ratio of 39-41:1.
[0013] Furthermore, in step (3), the single screw extruder is set with a zone temperature of 160-165℃, a zone temperature of 160-180℃, a zone temperature of 180-200℃, a die temperature of 170-190℃, a screw speed of 80-100rpm, and a length-to-diameter ratio of 28-30:1.
[0014] Furthermore, in step (3), the cooling roller is at 25-30°C.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. This solution utilizes nano-titanium dioxide and nano-zinc oxide as inorganic UV blockers. These two nanomaterials, through their specific semiconductor band structure, can effectively absorb and scatter UV photons. After modification and grafting with γ-glycidyl etheroxypropyltrimethoxysilane, the dispersion uniformity of nano-titanium dioxide and nano-zinc oxide in the matrix is improved. Simultaneously, it is combined with 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole organic UV absorber. The benzotriazole functional group in this molecular structure can convert UV energy into heat energy dissipation through intramolecular hydrogen bonding. Through reflection, scattering, and absorption of UV rays, long-lasting UV protection for automotive paint is achieved. Detailed Implementation
[0016] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0017] A protective film for automotive paint, the protective film being prepared from an ultraviolet (UV) blocker, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole UV absorber, antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, and antioxidant tris(2,4-di-tert-butylphenyl) phosphite; wherein the UV blocker is prepared from nano-titanium dioxide, nano-zinc oxide, aqueous ethanol solution, γ-glycidyl etheroxypropyltrimethoxysilane, and acetic acid.
[0018] Where specific experimental steps or conditions are not specified in the examples, they can be performed according to the conventional experimental steps or conditions described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products. Example 1:
[0019] (1) Nano-titanium dioxide with a particle size of 20 nm and nano-zinc oxide with a particle size of 20 nm were added to a 50% ethanol aqueous solution and treated with an ultrasonic device with a power of 500 W for 30 minutes. Then, γ-glycidoxypropyltrimethoxysilane was added, and the pH value was adjusted to 4 with acetic acid. The mixture was stirred in a sealed container at 50 °C and 200 rpm for 3 hours. After filtration, the mixture was washed twice with anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 70 °C for 4 hours to obtain an ultraviolet blocking agent. The mass ratio of nano-titanium dioxide, nano-zinc oxide, ethanol aqueous solution and γ-glycidoxypropyltrimethoxysilane was 5:5:100:4.
[0020] (2) The UV blocker obtained in step (1), thermoplastic polyurethane elastomer particles with a number average molecular weight of 80,000, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole UV absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite were put into a mixer and mixed at 800 rpm for 10 minutes at room temperature to obtain a premix. The premix was fed into a twin-screw extruder for melt blending and granulation. The processing temperature range of the twin-screw extruder was set as follows: Zone 1 160℃, Zone 2 165℃, Zone 3 170℃, Zone 4 175℃, and Die Head 180℃. The screw speed was 200 rpm and the length-to-diameter ratio was 39:1. After extrusion, water cooling and pelletizing, the composite functional masterbatch was obtained. The mass ratio of the ultraviolet blocking agent, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite is 15:70:3:0.5:0.5.
[0021] (3) The composite functional masterbatch obtained in step (2) is mixed with thermoplastic polyurethane elastomer particles with a number average molecular weight of 80,000 at a mass ratio of 1:3. The mixture is then added to a single screw extruder. The single screw extruder is set with a zone temperature of 160°C, a zone temperature of 160°C, a zone temperature of 180°C, a die temperature of 170°C, a screw speed of 80 rpm, and a length-to-diameter ratio of 28:1. The melt is cast through a T-die to a cooling roller at 25°C to form a protective film with a thickness of 0.2 mm. Example 2:
[0022] (1) Nano-titanium dioxide with a particle size of 25 nm and nano-zinc oxide with a particle size of 25 nm were added to an ethanol aqueous solution with a mass fraction of 55%. The solution was treated with an ultrasonic device with a power of 550 W for 35 minutes. Then, γ-glycidoxypropyltrimethoxysilane was added, and the pH value was adjusted to 4.5 with acetic acid. The solution was stirred in a sealed container at 55 °C and 250 rpm for 3.5 hours. The solution was filtered and washed three times with anhydrous ethanol. Then, it was placed in a vacuum drying oven and vacuum dried at 75 °C for 5 hours to obtain an ultraviolet blocking agent. The mass ratio of nano-titanium dioxide, nano-zinc oxide, ethanol aqueous solution and γ-glycidoxypropyltrimethoxysilane was 10:10:150:5.
[0023] (2) The ultraviolet blocking agent obtained in step (1), thermoplastic polyurethane elastomer particles with a number average molecular weight of 115,000, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite were added into a mixer and mixed at a speed of 1000 rpm. The mixture was stirred at room temperature for 12.5 minutes to obtain a premix. The premix was then fed into a twin-screw extruder for melt blending and granulation. The processing temperature range of the twin-screw extruder was set as follows: Zone 1 162.5℃, Zone 2 167.5℃, Zone 3 172.5℃, Zone 4 177.5℃, and Die Head 182.5℃. The screw speed was 300 rpm and the length-to-diameter ratio was 40:1. After extrusion, water cooling, and pelletizing, the composite functional masterbatch was obtained. The mass ratio of the ultraviolet blocking agent, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite is 20:75:5.5:1.25:1.25.
[0024] (3) The composite functional masterbatch obtained in step (2) is mixed with thermoplastic polyurethane elastomer particles with a number average molecular weight of 115,000 at a mass ratio of 1:4. The mixture is then added to a single-screw extruder. The single-screw extruder is set with a zone temperature of 162°C, a zone temperature of 170°C, a zone temperature of 190°C, a die temperature of 180°C, a screw speed of 90 rpm, and a length-to-diameter ratio of 29:1. The melt is cast through a T-die to a cooling roller at 27.5°C to form a protective film with a thickness of 0.2 mm. Example 3:
[0025] (1) Nano-titanium dioxide with a particle size of 30 nm and nano-zinc oxide with a particle size of 30 nm were added to an ethanol aqueous solution with a mass fraction of 60%. The mixture was treated with an ultrasonic device with a power of 600 W for 40 minutes. Then, γ-glycidoxypropyltrimethoxysilane was added, and the pH value was adjusted to 5 with acetic acid. The mixture was stirred in a sealed container at 60 °C and 300 rpm for 4 hours. The mixture was filtered, washed 4 times with anhydrous ethanol, and then placed in a vacuum drying oven and vacuum dried at 80 °C for 6 hours to obtain an ultraviolet blocking agent. The mass ratio of nano-titanium dioxide, nano-zinc oxide, ethanol aqueous solution and γ-glycidoxypropyltrimethoxysilane was 15:15:200:6.
[0026] (2) The UV blocker obtained in step (1), thermoplastic polyurethane elastomer particles with a number average molecular weight of 150,000, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole UV absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite were put into a mixer and mixed at 1200 rpm for 15 minutes at room temperature to obtain a premix. The premix was fed into a twin-screw extruder for melt blending and granulation. The processing temperature range of the twin-screw extruder was set as follows: Zone 1 165℃, Zone 2 170℃, Zone 3 175℃, Zone 4 180℃, and Die Head 185℃. The screw speed was 400 rpm and the length-to-diameter ratio was 41:1. After extrusion, water cooling and pelletizing, the composite functional masterbatch was obtained. The mass ratio of the ultraviolet blocking agent, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and antioxidant tris(2,4-di-tert-butylphenyl) phosphite is 25:80:8:2:2.
[0027] (3) The composite functional masterbatch obtained in step (2) is mixed with thermoplastic polyurethane elastomer particles with a number average molecular weight of 150,000 at a mass ratio of 1:5. The mixture is then added to a single screw extruder. The single screw extruder is set with a zone temperature of 160°C, a zone temperature of 180°C, a zone temperature of 200°C, a die temperature of 190°C, a screw speed of 100 rpm, and a length-to-diameter ratio of 30:1. The melt is cast through a T-die to a cooling roller at 30°C to form a protective film with a thickness of 0.2 mm.
[0028] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that nano-titanium dioxide is not added.
[0029] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that nano zinc oxide is not added.
[0030] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the nano-titanium dioxide and nano-zinc oxide are not modified.
[0031] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that no ultraviolet blocking agent is added.
[0032] Tensile strength was tested according to GB / T1040.3-2006; light transmittance was tested according to GB / T2410-2008; weather resistance was tested by xenon lamp aging for 1000 hours according to GB / T16422.2-2022, and then color difference was detected by spectrophotometer.
[0033] Table 1 below shows the performance analysis results of the embodiments and comparative examples of the present invention.
[0034] Table 1 Sample number Tensile strength (MPa) Light transmittance (%) Color difference (ΔE) after xenon lamp aging for 1000 hours Example 1 46.5 90.8 1.52 Example 2 48.2 91.5 1.38 Example 3 47.8 90.2 1.61 Comparative Example 1 44.1 91.0 3.85 Comparative Example 2 43.8 90.5 4.12 Comparative Example 3 39.3 86.4 5.97 Comparative Example 4 42.5 92.3 8.46 Experimental data from the examples and comparative examples show that the present invention uses modified nano-titanium dioxide and modified nano-zinc oxide as inorganic ultraviolet blocking agents, and benzotriazole ultraviolet absorbers as organic ultraviolet absorbers. Nano-titanium dioxide and nano-zinc oxide mainly reflect and scatter UVB and UVA bands respectively through their semiconductor properties. At the same time, the hydrogen bonds in the molecular structure of benzotriazole ultraviolet absorbers undergo isomerization after absorbing high-energy ultraviolet rays and convert the energy into heat energy for dissipation, thereby achieving long-term ultraviolet protection for automotive paint.
[0035] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. An automotive paint protection film, characterized by, The protective film is prepared from an ultraviolet blocking agent, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester and antioxidant tris(2,4-di-tert-butylphenyl) phosphite; the ultraviolet blocking agent is prepared from nano-titanium dioxide, nano-zinc oxide, an ethanol aqueous solution, γ-glycidoxypropyltrimethoxysilane and acetic acid.
2. The automotive paint protection film of claim 1, wherein: The nano-zinc oxide has a particle size of 20-30 nm.
3. The automotive paint protection film of claim 2, wherein: The nano-titanium dioxide has a particle size of 20-30 nm.
4. The automotive paint protection film of claim 3, wherein: The thermoplastic polyurethane elastomer particles have a number average molecular weight of 80000-150000.
5. The method of claim 4, wherein the film is prepared by coating a base film with a primer layer, a first adhesive layer, a first protective layer, a second adhesive layer, a second protective layer, and a third adhesive layer in this order. The method comprises the following steps: (1) the nano-titanium dioxide and nano-zinc oxide are added into an ethanol aqueous solution with a mass fraction of 50-60%, and then treated by an ultrasonic device with a power of 500-600 W for 30-40 minutes, then γ-glycidoxypropyltrimethoxysilane is added, acetic acid is used to adjust the pH value to 4-5, and then stirring is carried out in a sealed container at 50-60 ℃ and a rotating speed of 200-300 rpm for 3-4 hours, then the product is extracted, washed with anhydrous ethanol for 2-4 times, and then dried in a vacuum drying box at 70-80 ℃ for 4-6 hours to obtain the ultraviolet blocking agent; (2) the ultraviolet blocking agent obtained in step (1), thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester and antioxidant tris(2,4-di-tert-butylphenyl) phosphite are put into a mixer, mixed at a rotating speed of 800-1200 rpm and room temperature for 10-15 minutes to obtain a premix; the premix is put into a double-screw extruder for melt blending and granulation, and then extruded, cooled in a water tank and cut into particles to obtain a composite functional masterbatch; (3) the composite functional masterbatch obtained in step (2) is mixed with thermoplastic polyurethane elastomer particles at a mass ratio of 1:(3-5), and then the mixture is put into a single-screw extruder, the melt is cast onto a cooling roller through a T-shaped die to form a protective film.
6. The method for preparing an automotive paint protection film according to claim 5, characterized in that: In step (1), the mass ratio of the nano-titanium dioxide, nano-zinc oxide, ethanol aqueous solution and γ-glycidoxypropyltrimethoxysilane is (5-15):(5-15):(100-200):(4-6).
7. The method for preparing an automotive paint protection film according to claim 5, characterized in that: In step (2), the mass ratio of the ultraviolet blocking agent, thermoplastic polyurethane elastomer particles, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole ultraviolet absorber, antioxidant tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester and antioxidant tris(2,4-di-tert-butylphenyl) phosphite is (15-25):(70-80):(3-8):(0.5-2):(0.5-2).
8. The method for preparing an automotive paint protection film according to claim 5, characterized in that: The processing temperature range of the twin-screw extruder in step (2) is set as: zone 1 160-165°C, zone 2 165-170°C, zone 3 170-175°C, zone 4 175-180°C, and the die head 180-185°C, the screw rotation speed is 200-400 rpm, and the length-diameter ratio is 39-41:
1.
9. The method for preparing an automotive paint protection film according to claim 5, characterized in that: In step (3), the single-screw extruder is set as zone 1 temperature 160-165°C, zone 2 temperature 160-180°C, zone 3 temperature 180-200°C, die head temperature 170-190°C, screw rotation speed 80-100 rpm, and length-diameter ratio 28-30:
1.
10. The method for preparing an automotive paint protection film according to claim 5, characterized in that: In step (3), the cooling roller is 25-30°C.
Citation Information
Patent Citations
A hydrophobic and antifouling automobile paint protective film and preparation method thereof
CN118755122B